Hubungan Pemberian Edukasi Penyakit Skabies terhadap Tingkat Pengetahuan dan Perilaku Santri di Pondok Pesantren Darul Mujahadah - Juniarti, Nabilla Eka; Farida Fakhrunnisa; Arifina Fahamsya; Endang Istriningsih (STIKes Ibnu Sina Ajibarang, 2026)
Scabies is a contagious skin infestation that is highly prevalent in densely populated environments, such as Islamic boarding schools (pesantren). The primary factors contributing to its transmission are a significant lack of medical knowledge and poor hygiene behavior among residents. This study aims to analyze the impact of educational interventions on the knowledge levels and hygiene behaviors of students (santri). The research employed a pre-experimental method with a one-group pretest-posttest design. A total of 109 students at Darul Mujahadah Islamic Boarding School were selected as the study sample using a purposive sampling technique based on specific inclusion criteria. The results demonstrated a significant increase in the average knowledge score from 57,49 (pre-test) to 65,40 (post-test) with a p-value of 0,000. Similarly, the average behavior score significantly improved from 27,58 (pre-test) to 31,24 (post-test) (p-value 0,000). These findings indicate that the provision of health education significantly enhances students' knowledge levels and fosters more positive behavioral changes regarding the prevention and management of scabies within the boarding school environment.